2020
DOI: 10.1002/smll.202001207
|View full text |Cite
|
Sign up to set email alerts
|

A Graphene‐Based Supramolecular Nanoreactor for the Fast Synthesis of Imines in Water

Abstract: The confinement of organic synthesis within waterborne nanoreactors is regarded with increasing attention to improve its yield and reduce the environmental impact. However, many catalysts, such as graphene, are barely dispersible in aqueous media and many chemical reactions cannot be performed in the presence of water due to thermodynamic limitations. Therefore, there is an urgent need to develop novel strategies to carry out these processes in more sustainable conditions. To pursue this goal, in this work, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The well-known carbon materials are not “innocent” supports, as demonstrated by many recent publications within the carbocatalysis field. As a matter of fact, recently, they have emerged as cheap and metal-free catalysts and have attracted much attention regarding the use of graphite, graphite oxide (GO), and graphene oxide (eGO) in the oxidation reaction, Friedel–Crafts reaction, aza-Michael addition, imination, polymerization, epoxy-ring opening reactions, , Mukaiyama–Michael reaction, , and crosslinking reaction …”
Section: Introductionmentioning
confidence: 99%
“…The well-known carbon materials are not “innocent” supports, as demonstrated by many recent publications within the carbocatalysis field. As a matter of fact, recently, they have emerged as cheap and metal-free catalysts and have attracted much attention regarding the use of graphite, graphite oxide (GO), and graphene oxide (eGO) in the oxidation reaction, Friedel–Crafts reaction, aza-Michael addition, imination, polymerization, epoxy-ring opening reactions, , Mukaiyama–Michael reaction, , and crosslinking reaction …”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has shown that graphene layers functionalized with Scheme 54 Fluorogenic reaction of imine formation from anime salt and aldehyde, performed in water using surfactants as reported by Ladame et al 89 Scheme 55 Condensation of amines and aldehydes in a polymeric micelle from the self-assembly of pyrrole-based amphiphilic block copolymers as reported by Palmiero et al (HSAG-SP: high surface area graphiteserinol pyrrole, PEG-EP 10 : polyethylene glycol chain extended with 10 ethanol pyrrole methacrylate units). 90 Scheme 53 Oxidative homocoupling of octylamine in DDAO (dimethyldodecylamine N-oxide) surfactant solvent as reported by Savelli et al 88…”
Section: Imine Synthesis In Water (Micellar Media)mentioning
confidence: 97%
“…In 2020, Palmiero et al reported using a micelle derived from pyrrole-based amphiphilic block copolymers with graphene for the condensation of carbonyls and amines to form imines (Scheme 55). 90 The aldehyde and amine were mixed in equimolar amounts. Graphene is a powerful catalyst for acid-catalysed reactions due to its high π-electron density, but it tends to form counterproductive agglomerates.…”
Section: Imine Synthesis In Water (Micellar Media)mentioning
confidence: 99%
“…54,55 As compared to other supports, GO's 2D framework facilitates open access to reactants with limited mass transfer impedance 56 and it has been called a nano-reactor. 57,58 GO and its nanocomposites are finding applications in biomedical devices, 59 hydrogen storage, 60 drug delivery, 61 super-capacitors 62 and waste-water treatment. 63 A large number of GO-based nanocatalysts are prepared by immobilization of metal NPs, metal oxides, metal complexes, etc.…”
Section: Introductionmentioning
confidence: 99%